Strategy and Uncertainty: Resource-Based View, Strategy-Creation View, and the Hybrid Between Them - Furr, Nathan R.; Eisenhardt, Kathleen M. (Journal of Management, 2021)
The resource-based view (RBV) makes a significant contribution to strategy by explaining the relationship between resources and firm performance. Particularly in low uncertainty markets, executives have the foresight and time to build strategically valuable resources in current markets and leverage them into related markets. RBV is also relevant for understanding strategies for market entry, extending the value of technology resources, and broadening the locus of resources within ecosystems. Conversely, in high uncertainty markets like nascent or disrupted ones, RBV seems less germane. Resources may not yet exist or their value (and rarity) may be indeterminate (or changing). Here, we contribute the Strategy Creation (SC) view—joining strategizing by doing, thinking, and shaping. It offers a strategic logic that fits highly uncertain markets. Finally, we contribute the insight that RBV and SC are complements under moderate uncertainty, such as growth markets and technology transitions. Overall, we propose that uncertainty forms a crucial boundary condition for RBV that distinguishes between qualitatively different strategic logics.